The Manning grooms - Macomber, Debbie. frey50 (Don Mills, Ont. : Mira, 2008)
A two-in-one volume. In Bride on the Loose Jason Manning is content with his life as a bachelor, a slob and a sports fan. Then a precocious girl named Carrie Weston decides to play matchmaker, introducing him to her mother, Charlotte. In Same Time Next Year James Wilkens spends New Year's Eve in Las Vegas...where he meets Summer Lawton after his broken engagement with a Manning sister.
Bride on the loose -- Same time, next year.
Originally published separately: Bride on the loose, c1992 ; Same time, next year, c1995.
Keywords: Man-woman relationships; Bachelors; Marriage